Ethics and business an introduction - Gibson, Kevin, 1955- (Cambridge ; New York : Cambridge University Press, 2007)
"In this book, Kevin Gibson explores the relationship between ethics and the world of business, and how we can serve the interests of both. He builds a philosophical groundwork that can be applied to a wide range of issues in ethics and business, and shows readers how to assess dilemmas critically and work to resolve them on a principled basis. Using case studies drawn from around the world, he examines topics including stakeholder responsibilities, sustainability, corporate social responsibility, and women and business. Because business can no longer be isolated from its effects on communities and the environment, these concerns are brought to the forefront. The book also captures the dynamic nature of business ethics in the era of globalization where jobs can be outsourced, products are made of components from scores of countries, and sweatshops often provide the cheap goods the public demands."--Jacket.
An overview of business ethics -- Insights from ethical theory -- The capitalist system and its ethical implications -- Feminism -- Responsibility -- Rights -- Autonomy -- Beneficence -- The environment.
Includes bibliographical references and index.
Description based on print version record.
Keywords: Business ethics; Social responsibility of business; Corporate profits -- Moral and ethical aspects; Business enterprises -- Environmental aspects; Globalization -- Moral and ethical aspects; Business ethics -- Case studies; Bedrijfsleven; Ethiek; Unternehmensethik; Wirtschaftsethik; BUSINESS & ECONOMICS / Business Ethics; Fallstudiensammlung; Electronic books